Core immune cell infiltration signatures identify molecular subtypes and promote precise checkpoint immunotherapy in cutaneous melanoma - Zhu, Zheng; Li, Guoyin; Li, Zhenning; Wu, Yinghua; Yang, Yan; Wang, Mingyang; Zhang, Huihua; Qu, Hui; Song, Zewen; He, Yuanmin (Frontiers in Immunology, 2022)
Tumor microenvironment (TME) has been shown to impact the prognosis of tumors in patients including cutaneous melanoma (CM); however, not all components of TME are important. Given the aforementioned situation, the functional immune cell contents correlated with CM patient prognosis are needed to optimize present predictive models and reflect the overall situation of TME. We developed a novel risk score named core tumor-infiltrating immune cell score (cTICscore), which showed certain advantages over existed biomarkers or TME-related signatures in predicting the prognosis of CM patients. Furthermore, we explored a new gene signature named cTILscore-related module gene score (cTMGs), based on four identified TME -associated genes (GCH1, GZMA,PSMB8 and PLAAT4) showing a close correlation with the cTICscore, was generated by weighted gene co-expression network analysis and least absolute shrinkage and selection operator analysis to facilitate clinical application. Patients with low cTMGs had significantly better overall survival (OS, P = 0.002, < 0.001, = 0.002, and = 0.03, respectively) in the training and validating CM datasets. In addition, the area under the curve values used to predict the immune response in four CM cohorts were 0.723, 0.723, 0.754, and 0.792, respectively, and that in one gastric cohort was 0.764. Therefore, the four-gene signature, based on cTICscore, might improve prognostic information, serve as a predictive tool for CM patients receiving immunotherapy.